ADVERTISING CAMPAIGN OF HIGHER EDUCATION INSTITUTION DEVELOPMENT BASICS - Natela R. Kordzaia (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
Today in Ukraine there are such processes as the reduction of the number of entrants to higher education institutions due to demographic reasons, due to going to study in other countries or due to reducing the number of budget places and increasing the cost of training. All these processes stimulates the intensification of competition in the market of educational services. The problem of most universities in our country is the lack of a clear strategic approach to managing their competitiveness in today’s market. The main task of developing a competitive strategy of higher education institutions is, first of all, efficient and reasonable distribution of resource potential and adaptation to the external environment in the modern market of educational services. The purpose of the article is to develop proposals for an effective plan for the advertising campaign of higher education institutions. The strategy of the advertising campaign of a higher education institution, today, is determined by the specifics of the university and the peculiarities of its educational process. The main content of the advertising campaign should be informational and explanatory. It is necessary to convey the maximum of special information to the object of advertising influence. All communication within the advertising campaign of a higher education institution is aimed primarily at improving such elements as image, reputation, brand and more. This idea should do everything to make the target audience so interested in the higher that any contact took place. This contact can be, for example, going to a website, going to a social networking group, calling, or even visiting the higher education institution itself. The mechanisms for calculating and translating the values aimed at increasing marketing actions into the exact financial equivalent have not yet been worked out. This should be taken into account when planning activities to assess the effectiveness of the university’s advertising campaign. The algorithm of conducting advertising campaigns of higher education institutions is developed in the article. The stages of this algorithm are as follows: determining the purpose and objectives of the advertising campaign; setting the objectives of the advertising campaign, determining the metrics (performance indicators) of the advertising campaign; characteristics of the target audience; research and analysis of advertising activities of competitors; research of the main channels and carriers of future advertising; conducting media planning (planning of advertising media, budget and deadlines); creating a creative idea of an advertising message; advertising production; control over the placement of advertising; evaluation of the effectiveness of the advertising campaign. The article also reveals the content of each of the stages of the algorithm. Each stage of the algorithm must be carefully thought out and worked out.